Association between the Triglyceride Glucose Index and Hyperuricemia in Patients with Primary Hypertension: A Cross-Sectional Study - Shanshan Liu; Zhixian Zhou; Miao Wu; Hao Zhang; Yao Xiao (International Journal of Endocrinology)
Objective. The aim of this study was to investigate the association between the triglyceride glucose (TyG) index and hyperuricemia (HUA) in patients with grades 1–3 hypertension. Study Design. This is a cross-sectional study. A total of 1,707 patients from the cardiovascular department of Affiliated Hospital of Jiangxi University of Traditional Chinese Medicine were studied. In this study, 899 patients with grades 1-2 hypertension were included, of which 151 had HUA; additionally, 808 patients with grade 3 hypertension were included, of which 162 patients had HUA. This study obtained all patient data from the electronic medical record system of the Affiliated Hospital of Jiangxi University of Traditional Chinese Medicine. The TyG index was calculated as Ln (triglycerides × fasting glucose/2). Hyperuricemia was defined as uric acid ≥420 μmol/L (7 mg/dL). Multivariate logistic regression, penalized spline regression, and generalized additive models were used to evaluate the association between the TyG index and HUA. Stratified analyses were performed to assess the association in populations with different grades of hypertension. Results. The average TyG index was 8.71 ± 0.58. After adjusting for correlated variables, the logistic regression analysis revealed a positive correlation between the TyG index and HUA (OR = 1.83; 95% CI: 1.40–2.39). Smooth curve fitting showed that this correlation was linear in the whole range of the TyG index. In the subgroup analysis, the TyG index more strongly associated with HUA in the grades 1-2 hypertension group (OR = 2.22; 95% CI: 1.44–3.42) compared to that in the grade 3 hypertension group (OR = 1.58; 95% CI: 1.11–2.24; P for interaction = 0.03). In addition, this association was consistent in all models. Conclusion. The TyG index was positively associated with HUA in patients with hypertension, and the association was more strongly confirmed in those with grades 1-2 hypertension rather than in those with grade 3 hypertension.